Management of drought-relief maize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Management of drought-relief maize by PS Tyler, D J Walker and TJ Donaldson 1994 35pp ISBN 0 85954 374 9 Price UKL5.00 NRI, Central Avenue, Chatham Maritime, Kent ME4 4TB, UK